Has the digital divide been reversed? Evidence from five EU countries - Smaranda Pantea; Bertin Martens (European Commission, Joint Research Centre (JRC), 2013)
This paper examines whether there is a digital divide in the use of the internet in general and for specific purposes (leisure, improving human capital and obtaining goods and services). It uses a unique dataset which covers the entire clickstream of almost 20,000 internet users in the five largest EU economies during 2011. Our main finding is that, for those who have access to the Internet, the income-based digital divide in internet use has been reversed. Low-income internet users spend more time on the internet than high-income users. In addition, we find that employment status does not change the effect of income on internet use and we discuss several possible explanations for this result. There is some evidence of an education-based digital divide in the use of human capital and goods & services websites. Tertiary education has a negative effect on time spent on leisure websites and a positive effect on time spent on human capital and goods & services websites. Using quantile regressions, we find that the negative effect of income and the positive effect of education for human capital and goods & services websites hold for the entire conditional distribution of these online activities. Moreover, these effects are stronger for more intensive internet users.
Keywords: L86; D12; D13; 330; Internet Use; Time allocation; Leisure; digital divide